2004
DOI: 10.1002/ana.20334
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral limbic diffusion abnormalities in unilateral temporal lobe epilepsy

Abstract: Diffusion tensor magnetic resonance imaging can acquire quantitative information on the microstructural integrity of white matter structures and depict brain connectivity in vivo based on the behavior of water diffusion. Diffusion tensor imaging-derived tractography has been used for virtual dissection of the fornix and cingulum in healthy subjects, but not in patients with temporal lobe epilepsy (TLE). Eight patients with medically intractable TLE and unilateral mesial temporal sclerosis and nine healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
211
5
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 245 publications
(248 citation statements)
references
References 45 publications
(116 reference statements)
22
211
5
2
Order By: Relevance
“…It must be noted, however, that the fimbriafornix is a bidirectional pathway, including afferents to the mesial temporal region from a variety of structures including the septum and that other sources of axonal degeneration are also possible. Our previous DTI tractography studies showed bilateral water diffusion abnormalities of the fimbria-fornix in TLEϩuMTS patients (Concha et al, 2005b(Concha et al, , 2009, in excellent agreement with a recent postmortem study confirming decreased axonal density of the fimbria-fornix bilaterally in four TLEϩuMTS patients (Ozdogmus et al, 2009) As ipsilateral but not contralateral fimbria-fornix abnormalities would be expected if the reduced fimbria-fornix integrity was solely secondary to degeneration of mesial temporal efferent fibers, the bilateral findings suggest that degeneration of efferent fibers may not be the only mechanism responsible for the observed changes. Ozdogmus et al reported that myelinated axons greatly outnumbered unmyelinated axons in the fimbriafornix of both TLE patients and normal controls (Ozdogmus et al, 2009), while we found a near complete absence of unmyelinated axons in TLEϩuMTS and TLEϪMTS patients.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…It must be noted, however, that the fimbriafornix is a bidirectional pathway, including afferents to the mesial temporal region from a variety of structures including the septum and that other sources of axonal degeneration are also possible. Our previous DTI tractography studies showed bilateral water diffusion abnormalities of the fimbria-fornix in TLEϩuMTS patients (Concha et al, 2005b(Concha et al, , 2009, in excellent agreement with a recent postmortem study confirming decreased axonal density of the fimbria-fornix bilaterally in four TLEϩuMTS patients (Ozdogmus et al, 2009) As ipsilateral but not contralateral fimbria-fornix abnormalities would be expected if the reduced fimbria-fornix integrity was solely secondary to degeneration of mesial temporal efferent fibers, the bilateral findings suggest that degeneration of efferent fibers may not be the only mechanism responsible for the observed changes. Ozdogmus et al reported that myelinated axons greatly outnumbered unmyelinated axons in the fimbriafornix of both TLE patients and normal controls (Ozdogmus et al, 2009), while we found a near complete absence of unmyelinated axons in TLEϩuMTS and TLEϪMTS patients.…”
Section: Discussionmentioning
confidence: 81%
“…in all voxels in the brain having a fractional anisotropy (FA) threshold Ͼ0.3, and was terminated if the propagating streamlines entered voxels of low anisotropy (FA Ͻ 0.3) or deviated by Ͼ70°. The fimbria-fornix was virtually dissected by the extraction of those tracts that intersected two manually placed regions of interest (Concha et al, 2005b). Fractional anisotropy was averaged for the voxels lying between the level of the mammillary bodies and the fusion of the crura of the fornices, exactly as we have performed in our previous DTI studies of TLE (Concha et al, 2005a(Concha et al, ,b, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nas últimas décadas, o grande desenvolvimento tecnológico das técnicas de imagem (Basser et al, 1994;Cercignani et al, 2001;Concha et al;Jellison et al,2004;Ciccarelli et al, 2005;Voegts et al, 2006;Cho et al;Kubicki et al, 2007) e monitorização da função cerebral, in vivo, (Clarck et al,2003;Berman et al, 2004Berman et al, , 2007Kamada et al, 2005) evidenciou a necessidade de um substrato anatômico para corroborar seus achados. Tal fato, revitalizou o estudo das dissecções das fibras brancas cerebrais e resgatou a história da neuroanatomia (Ture et al, 1997(Ture et al, ,2000.…”
Section: Revisão Da Literaturaunclassified
“…As informações das alterações quantitativa e qualitativa da difusão de moléculas de água tem influenciado a compreensão sobre a conectividade cerebral e permitido inferir sobre a fisiopatologia e possíveis intervenções terapêuticas em diversas patologias como epilepsia (Concha et al,2005), doenças cerebrovasculares (Voegts et al, 2006;Cho et al,2007), esclerose múltipla (Cercignani et al, 2001;Ciccarelli et al, 2005), esclerose lateral amiotrófica (Ciccarelli et al, 2006) e distúrbios neuropsiquiátricos (Kubicki et al, 2007). A aplicação da tractografia também tem influenciado a neurocirurgia, principalmente no que concerne o planejamento e estratégias de ressecções cirúrgicas em lesões intrinsicas cerebrais.…”
Section: Histórico Da Técnica De Dissecção De Fibrasunclassified